Mediating role of attitude in green purchase intention for solar power plants: A green marketing analysis - Indrajaya, Nehemia; Perizade, Badia; Wahab, Zakaria; Shihab, Muchsin Saggaff (goodwood publishing, 2023)
Purpose: The principal objective of this study is to identify the factors that might influence the inclination towards eco-friendly purchases while considering the incorporation of renewable energy via Solar Power Generation Systems (PLTS). Research Methodology: A comprehensive data analysis was conducted using a Structural Equation Model (SEM) facilitated by the SMART PLS. This study targets household electricity consumers in Palembang, Indonesia. Results: The findings indicate that Environmental Knowledge has a significant impact on Green Purchase Intention, whereas green product awareness plays a notable role in influencing green purchase intention. Moreover, it was found that attitude did not significantly affect Green Purchase Intention. Green Product Awareness has a substantial effect on green purchase intentions. Notably, this study establishes that Environmental Knowledge does not impact Green Purchase Intention through attitude, indicating partial mediation. The findings of this study emphasize the critical role of Environmental Knowledge and Green Product Awareness in shaping green purchase intentions among electricity consumers in Palembang, Indonesia. Limitations: Fostering an environment that is conducive to enhancing environmental literacy and promoting awareness of green products is imperative. Contribution: This research explores the various elements that impact the likelihood of making eco-conscious purchases, particularly in relation to embracing renewable energy technologies.